MONETARY EXPANSION AND ECONOMIC GROWTH IN NEPAL: A VECM APPROACH - Gyan Mani Adhikari; Achyut Gnawali; Binod Joshi (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
Modeling the relationship between money supply and national output has been one of the main controversial issues of interest for economists, researchers, and policymakers, over the past few years.. Economies worldwide aim to achieve a high output growth rate and stability in the general price level. There are debates between Keynesian and monetarists about the relationship direction between money supply and output. Monetarists argue that changes in the amount of money lead to unexpected changes in nominal income because of money stability. In contrast, Friedman assumes that it is the most stable function. The paper aims to analyze the process of money supply determination in Nepal and to analyze the short-run and long-run relation between money supply and economic growth in Nepal, using time series data, spanning from 1975 to 2023. The econometric model used in this study has been developed based on the quantity theory of money model, but the model is modified to accommodate other independent variables that influence economic growth. The study reveals that the money multiplier in Nepal is constant and also affected by the cash reserve ratio, indicating that the monetary policy variables can influence the money supply in the case of Nepal. Engle-Granger cointegration results reveal that there exists a long-run relationship between real GDP with broad money supply (M2) and narrow money supply (M1) at a 1 percent level of significance and with gross fixed capital formation (GFCF) at a 5 percent level of significance, but the results show that there is no any long-run relationship between real GDP and government capital expenditure. The VCEM results show that NGDP as a dependent variable was observed to be statistically significant with broad money supply (M2), at a 10 percent level of significance, implying the existence of long-run causality was observed from broad money supply to real GDP.